PENGEMBANGAN SISTEM PERHITUNGAN ANGKA KREDIT PADA DUPAK JABATAN FUNGSIONAL WIDYAISWARA BERBASIS WEB - Fadillah, Nanda Lidya; Vivianti, Vivianti (Jurnal Edukasi Elektro, 2022)
ABSTRACT:This study aims to develop a Credit Score Calculation System for the Widyaiswara Functional Dupak at the Makassar Religious Education and Training Center. This research is expected to produce a good and efficient system. The type of research from the development of a credit score calculation system uses the type of research and development or Research and Development (R&D). This research model uses the Waterfall development model. This model has four stages of development including analysis, design, code, testing, and maintenance. The system development process uses several programming languages as the main tools including the PHP programming language, MySQL database, Bootstrap Framework and Codeigniter. The product that will be produced is a web-based application system with the main function as an application for calculating credit scores at the Widyaiswara Functional Dupak at the Makassar Religious Education and Training Center.ABSTRAK:Penelitian ini bertujuan untuk mengembangkan Sistem Perhitungan Angka Kredit pada Dupak Jabatan Fungsional Widyaiswara di Balai Diklat Keagamaan Makassar. Penelitian ini diharapkan mampu menghasilkan sistem yang baik dan efisien. Jenis penelitian dari pengembangan sistem perhitungan angka kredit menggunakan jenis penelitian dan pengembangan atau Research and Development (R&D). Model penelitian ini menggunakan jenis model pengembangan Waterfall. Model ini memiliki empat tahap pengembangan diantaranya adalah analysis, design, code, testing, dan maintenance. Proses pengembangan sistem menggunakan beberapa bahasa pemograman sebagai tools utama diataranya yaitu bahasa pemograman PHP, Database MySQL, Framework Bootsrap dan Codeigniter. Produk yang akan dihasilkan adalah sistem aplikasi berbasis web dengan fungsi utama adalah sebagai aplikasi perhitungan angka kredit pada Dupak Jabatan Fungsional Widyaiswara di Balai Diklat Keagamaan Makassar.